2020
DOI: 10.1021/acsami.0c05294
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarobust and Biomimetic Hierarchically Macroporous Ceramic Membrane for Oil–Water Separation Templated by Emulsion-Assisted Self-Assembly Method

Abstract: Reported herein is a novel ultrarobust and biomimetic hierarchically macroporous ceramic membrane that can achieve a high efficiency of up to 99.98% for oil−water separation, while the efficiency remains nearly unchanged even after 10 rounds of use and storage for up to 4 months. The macroporous ceramic membrane is prepared by combining surface hydrophobic coating with an emulsion-assisted template selfassembly of the modified Al 2 O 3 ceramic powder. The as-prepared ceramic membrane is a lightweight material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Recently, the construction of lightweight and high-strength Al 2 O 3 porous ceramics by utilizing emulsified oil as the sacrificial template has been reported. 13 The as-prepared Al 2 O 3 ceramic suspension has a very low viscosity owing to the addition of the oil phase in the system. Therefore, we choose such an emulsion self-assembly approach to fabricate the hierarchically porous ceramic microspheres by combination with the superwettability strategy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the construction of lightweight and high-strength Al 2 O 3 porous ceramics by utilizing emulsified oil as the sacrificial template has been reported. 13 The as-prepared Al 2 O 3 ceramic suspension has a very low viscosity owing to the addition of the oil phase in the system. Therefore, we choose such an emulsion self-assembly approach to fabricate the hierarchically porous ceramic microspheres by combination with the superwettability strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental procedures are described in the Supporting Information. The ceramic suspension was prepared as follows (Figure 1a): 13 first of all, the Al 2 O 3 aqueous colloidal suspension was sonicated and acidized (pH < 5) by adding HCl. Followed by ball milling of the Al 2 O 3 suspension for a whole night, propionic acid, as the surface modifier, was then added dropwise into the suspension under vigorous stirring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some newly developed hydrophobic materials have been used for oilwater separation due to the special selectivity toward oil and water. Many materials such as metal meshes, 16 membranes, 17 sponges, 18 and fabrics 19 can be modified into highly hydrophobic or super-hydrophobic as matrix materials to separate oil and water. For example, Liu et al 20 fabricated a durable super-hydrophobic stainlesssteel mesh using a facile solution immersion method.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated membrane had a pore diameter of 1.2 µm and showed 99% oil separation at a flow rate of 85 L/m 2 •h and pressure of 50 kPa. A porous MF aluminum ceramic membrane was applied by Liu et al for oil-water separation [10]; they reported 99.98% removal of emulsified oil.…”
Section: Introductionmentioning
confidence: 99%